Maternal mortality in adolescents and young adults: temporal trend and correlation with prenatal care coverage in the state of Bahia, Brazil, 2000-2020 - Lorena Ramalho Galvão; Maria Conceição Oliveira Costa; Silvana Granado Nogueira da Gama; Magali Teresópolis Reis Amaral; Djanilson Barbosa dos Santos; Naysa Farias Barros; Wanessa Oliveira Rosario (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective: to analyze the temporal trend of maternal mortality and correlate it with prenatal care coverage among adolescents and young adults, state of Bahia, Brazil, 2000-2020. Methods: this was an ecological time-series study and correlation between maternal deaths and prenatal care visits in 10-19 and 20-24 age groups, using the Mortality Information System; the trend analysis was performed by means of Prais-Winsten regression, according to race/skin color, timing and causes of death; and Spearman coefficient was used for correlation. Results: in the study period, 418 deaths among adolescents and 574 among young adults were recorded; maternal mortality ratio was 59.7 and 63.2 deaths/100,000 live births, with a significant decreasing trend (-2.2% and -2.9% respectively); it could be seen an inverse correlation between a higher number of prenatal care visits and maternal mortality in the age groups. Conclusion: maternal mortality showed a decreasing trend in the study period, but with high proportions of death; there was a significant correlation between prenatal care coverage and maternal mortality among adolescents and young adults.